Subgroups in language trajectories from 4 to 11 years: the nature and predictors of stable, improving and decreasing language trajectory groups. (1st September 2017) - McKean, Cristina; Wraith, Darren; Eadie, Patricia; Cook, Fallon; Mensah, Fiona; Reilly, Sheena
Abstract : Background: Little is known about the nature, range and prevalence of different subgroups in language trajectories extant in a population from 4 to 11 years. This hinders strategic targeting and design of interventions, particularly targeting those whose difficulties will likely persist. Methods: Children's language abilities from 4 to 11 years were investigated in a specialist language longitudinal community cohort ( N = 1, 910). Longitudinal trajectory latent class modelling was used to characterise trajectories and identify subgroups. Multinomial logistic regression was used to identify predictors associated with the language trajectories children followed. Results: Three language trajectory groups were identified: 'stable' (94% of participants), 'low‐decreasing' (4%) and 'low‐improving' (2%). A range of child and family factors were identified that were associated with following either the low‐improving or low‐increasing language trajectory; many of them shared. The low‐improving group was associated with mostly environmental risks: non‐English‐speaking background, social disadvantage and few children's books in the home. The low‐decreasing group was associated with mainly biological risks: low birth weight, socioemotional problems, lower family literacy and learning disability. Conclusions: By 4 years, services can be confident that most children with low language will remain low to 11 years. Using rigid cut‐points in language ability to target interventions is not recommended due to continued individual variability in language development. Service delivery models should incorporate monitoring over time, targeting according to language abilities and associated risks and delivery of a continuum of interventions across the continuum of need.